Extrapolations of Periwinkle Secondary Metabolites as Multitarget Inhibitor of Breast Cancer Proteins - Aparna Prasad (International Journal of Biochemistry and Biomolecule Research, 2023)
Objective: Breast cancer is considered one of the most common and dangerous forms of cancer. It is a significant public health issue on a global scale. The study estimates that 10.0 million people will die from cancer this year, and 19.3 million people will develop the disease overall (BC). In this computation approach, nowadays emphasizes new drug discovery, the target protein epidermal growth factor receptor (EGFR) (5UGB), estrogen receptor (ER) (2QGT), and PI3KA (4OYS) were chosen to perform molecular docking against the derivatives of periwinkle Catharanthus phytochemical and FDA-approved drugs. Its pharmacological characteristics and its therapeutic analysis were investigated. Methods: The study was based on a computational approach using different phytocompounds for evaluation of their inhibitory potential against the target proteins EGFR, ER, and PI3KA. The protein molecular docking was conducted systematically using IMPPAT, PubChem, PDB, Open Bable, BIOVIA Discovery Studio Visualizer, PDB sum generate, PyRx, and ADMETlab 2.0. Result: The docking result revealed that the ligands selected have the best binding affinity with all three target proteins. Conclusion: The ligands could potentially be used to treat breast cancer in future approaches for studying the urge ligands in vitro and in vivo analysis to create novel breast cancer inhibitors.
Keywords: ADMET; Catharanthus; EGFR; ER; PI3KA; breast cancer; lochnericine; lochnerinine; molecular docking; periwinkle; vindolininol